Wear-resistant and highly thermally conductive sintered alloys especially suitable for bearings and valve seat rings
The production of copper-based sintered bonds through powder metallurgy technology has solved the problems of copper alloys in the prior art with reduced strength and high friction resistance at high temperatures, and achieved high thermal conductivity and wear resistance, reducing production complexity and cost.
Patent Information
- Application Number
- CN202111260887.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-10-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-10-28
AI Technical Summary
Existing steel powder sintered metal for bearings and valve seat rings decreases strength at high temperatures and additional coating is required to reduce friction, resulting in production complexity and increased costs.
The copper-based sintered gold produced by powder metallurgy accounts for more than 55% of the copper-based powder in the mixture. Combined with the hard phase, solid lubricant and pressing additives, the sintered gold is formed by uniaxial compression and high-temperature sintering.
High thermal conductivity and wear resistance are achieved, friction resistance is reduced, heat resistance and wear resistance of the material are improved, and production complexity and cost are reduced.
Abstract
Description
Technical Field
[0001] The invention relates to a wear-resistant, highly thermally conductive sintered alloy based on copper produced by powder metallurgy, in particular for bearing and valve seat ring applications, wherein the sintered alloy is a powder mixture of copper-based powder, hard phase, solid lubricant and pressing additives. The invention also relates to the production and use of a wear-resistant, highly thermally conductive sintered alloy based on copper. Background Art
[0002] Currently, a wide variety of materials, so-called bearing metals, are used in sintered alloys to produce bearings, such as plain bearings, but also for valve seat rings. Bearing metals should have high strength and high resistance and should have as little frictional resistance as possible so that they reduce heat generation and wear. The alloy metals and their proportions should vary depending on the properties that are prioritized in the respective application.
[0003] In the prior art, steel powder sintered alloys are known for the above-mentioned applications, whose sintered pores are impregnated with oil and / or contain solid lubricants. A disadvantage of these sintered alloys for the production of bearings or valve seat rings is that the possible presence of counter-rotators usually requires coating. Universal alloys are also increasingly reaching their limits, in particular due to the rising temperatures of new internal combustion engines, since the strength of these alloys drops sharply with temperature.
[0004] The valve seat ring, i.e. the ring set at the opening of the inlet and outlet channels of the cylinder head, is not only subject to the hammering action of the valve, but also to the impact of hot explosion gases. This means that high thermal conductivity and high wear resistance are usually required at the same time.
[0005] Brass or bronze alloys are therefore particularly suitable for valve seat rings, since pure copper is not suitable as a bearing metal due to its low strength and high ductility. Other copper alloys that have the required hardness and strength as well as thermal conductivity are, for example, copper-beryllium alloys. However, beryllium has the disadvantage that this metal is very toxic and high safety standards must be observed during its production.
[0006] In order to increase the thermal conductivity of valve seat rings, it is known to provide them as sintered parts. The valve seat rings are therefore often infiltrated with copper during the sintering process, thereby achieving a higher thermal conductivity.
[0007] It is also possible to use multi-layer sintered seat rings. For this purpose, a seat ring with a wear-resistant material in the valve contact area and a seat ring with a high thermal conductivity material in the remaining area is combined. However, the required reduction in valve temperature caused by this is not significant. Only a reduction of about 3 K was calculated in the simulation, so that the reduction in component temperature at the valve during engine testing compared to a conventional seat ring could not be determined.
[0008] EP 1 975 260 A1 discloses a copper-based multilayer sintered sliding element which contains 0.5 to 20% by weight of tin, 0.1 to 35% by weight of manganese, 2 to 25% by weight of solid lubricants, and the remainder copper. This type of sintered sliding element has similar or higher sliding properties than copper-based lead-containing sintered sliding elements.
[0009] DE 10 2016 109 539 A1 discloses a valve seat ring produced by powder metallurgy, in which the supporting layer consists of a solidified copper matrix containing 0.25 to 20% by weight of solidified components, while the functional layer also consists of a solidified copper matrix containing 5 to 20% by weight of hard phases.
[0010] A disadvantage of the above-mentioned sliding elements or valve seat rings, respectively, is that the production of the first layer, the so-called supporting layer, must take place first, and the production of the second layer, the functional layer, must take place subsequently, which essentially results in additional method steps.
[0011] Finally, US Pat. No. 10344636B4 discloses a sintered valve seat ring for a high-efficiency engine with strong valve cooling and wear resistance. The production requires the use of copper powder with an average particle size of 45 μm or less and a purity of 99.5% or more, which is naturally disadvantageous to production costs. Summary of the invention
[0012] The object of the present invention is to provide a wear-resistant and highly thermally conductive sintered alloy, in particular for valve seat ring and bearing applications, which meets the usual requirements for sealing, dimensional stability and wear resistance.
[0013] This object is achieved by a wear-resistant, highly thermally conductive sintered alloy produced by powder metallurgy with copper as the basis, wherein the sintered alloy is a powder mixture of a copper-based powder, a hard phase with a total proportion of 8% by weight to 40% by weight, a solid lubricant with a total proportion of 0.4% by weight to 3.8% by weight, a pressing additive with a total proportion of 0.3% by weight to 1.5% by weight, and production-related impurities, characterized in that the powder mixture comprises at least 55% by weight of copper-based powder, preferably at least 65% by weight of copper-based powder, particularly preferably at least 70% by weight of copper-based powder.
[0014] Preferably, amide waxes or stearates are used as compression additives in a proportion of 0.3% to 1.5% by weight in total.
[0015] Advantages achieved by the invention In particular, according to the invention, the powder mixture combines the properties of copper-based materials in terms of thermal conductivity with the properties of known valve seat ring materials made of sintered alloys produced by powder metallurgy in terms of high wear resistance. In addition, powder components which increase strength, heat resistance or wear resistance can advantageously be added.
[0016] Surprisingly, the valve seat ring manufactured by the sintered alloy according to the invention exhibits improved heat dissipation from the valve to the cylinder head and improved heat distribution within the component. To further increase heat dissipation, sodium-filled hollow valves and / or materials with higher heat resistance can be additionally used.
[0017] The production of the sintered alloy is carried out by uniaxial pressing of the powder mixture into a green body, followed by sintering at a temperature of 850° C. to 1050° C. in a sintering atmosphere of a mixture of hydrogen and nitrogen and / or an endothermic gas. The endothermic gas (Endogas) is a mixture of carbon monoxide (CO, about 20% by volume), hydrogen (H2, about 40% by volume), carbon dioxide (CO2, about 0.3% by volume) and nitrogen.
[0018] An advantageous embodiment of the invention is shown in claim 2. The further development according to claim 2 makes it possible to increase the wear resistance. For this purpose, the hard phase preferably comprises one or more alloys known in the prior art from Fe-Mo, Fe-Mo-Si-Cr and / or Fe-Mo-Si-Cr-Ni-Mn (see Tribology Letters, Springer Verlag 2009), and production-related impurities. In particular, the use of molybdenum can increase the wear resistance, the use of chromium can increase the heat resistance, and the use of manganese can increase the tensile strength.
[0019] Another advantageous embodiment of the invention is as described in claim 3. The further development according to claim 3 makes it possible to reduce friction. For this purpose, the solid lubricant comprises one or more lubricants selected from the group consisting of sulfide solid lubricants, hexagonal boron nitride, graphite and / or calcium fluoride. The total proportion of lubricants is preferably 0.4% by weight to 3.8% by weight, particularly preferably 1.5% by weight to 2.5% by weight.
[0020] In a particularly preferred embodiment of the invention, the powder mixture comprises the following further elements: 0.5 to 15 wt.-% Zn, 0.5 to 12 wt.-% Sn, 0.5 to 5 wt.-% P, 0 to 15 wt.-% Mn, 0.2 to 5 wt.-% Si, 0 to 14 wt.-% Al, 0.1 to 15 wt.-% Ni, 0.5 to 8 wt.-% Fe, and production-related impurities.
[0021] The elements Zn, Sn, P, Mn, Al, Fe and Ni increase the strength of the alloy. The elements P and Mn increase the tensile strength and hardness in particular. The elements Si, Ni and Fe increase the heat resistance of the alloy. The elements Sn, Al and Mn increase the corrosion resistance and oxidation resistance.
[0022] In order to further increase the strength of the alloy, the alloying elements Mn and Al may optionally be present in a fraction of up to 20% by weight or in a fraction of 14% by weight.
[0023] In another particularly preferred embodiment of the present invention, the powder mixture contains at least 55 wt.-%, preferably at least 65 wt.-%, particularly preferably at least 70 wt.-% copper powder, and the following other elements and / or alloys: 1 wt.-% to 20 wt.-% Fe and / or Fe alloys, and / or 0 wt.-% to 8 wt.-% Co, and / or 1 wt.-% to 8 wt.-% Mo, and / or 0 wt.-% to 5 wt.-% Ni and / or Ni alloys.
[0024] Therefore, the elements Fe, Co, Mo and Ni increase the strength of the alloy. In addition, the Mo element also improves wear resistance. The Fe, Co and Ni elements increase the heat resistance of the alloy.
[0025] The alloy elements Co and Ni may optionally be present in a proportion of 8% by weight or 5% by weight, respectively, in order to further increase the heat resistance of the alloy.
[0026] In another particularly preferred embodiment of the present invention, the powder mixture contains at least 55 wt.-%, preferably at least 65 wt.-%, particularly preferably at least 70 wt.-% copper powder, and the following other elements and / or alloys: 1 wt.-% to 20 wt.-% Al and / or Al alloys, and / or 1 wt.-% to 8 wt.-% P and / or P alloys, and / or 1 wt.-% to 20 wt.-% Si and / or Si alloys.
[0027] Al and P elements increase the strength of the alloy, Si element increases the heat resistance of the alloy. Element P also increases the tensile strength and hardness of the alloy, and Al element increases the corrosion resistance and oxidation resistance of the alloy.
[0028] In another particularly preferred embodiment of the present invention, the powder mixture contains at least 55% by weight, preferably at least 65% by weight, particularly preferably at least 70% by weight of copper powder, and comprises the following further components: 2% to 14% by weight of zinc oxide or tin oxide, and / or 0.2% to 2% by weight of tungsten oxide, molybdenum oxide, copper oxide and bismuth oxide, respectively.
[0029] Additionally or alternatively, the powder mixture can also contain silicon nitride and / or silicon carbide in a proportion of 1% by weight to 14% by weight.
[0030] Zinc oxide, tin oxide, tungsten oxide, molybdenum oxide, copper oxide and bismuth oxide can improve wear resistance and act as solid lubricants. Silicon carbide and silicon nitride improve wear resistance.
[0031] The above-mentioned embodiments or their powder mixtures alone or in combination produce a wear-resistant, highly thermally conductive sintered alloy according to the invention produced by powder metallurgy with copper as the matrix.
[0032] After sintering, the sintered component may still contain pores. Such pores are generated, for example, by compacting the powder mixture to a relative density of typically 85% to 95% (instead of reaching 100% of the theoretical density) due to evaporation of the pressing additives during the sintering process or incomplete sintering. Thus, in particular, the residual porosity of the component can be adjusted by pressing / compacting. If the pores are interconnected, the residual pores can be impregnated with oil in order to improve the friction properties of the bearing, for example a plain bearing or a valve seat ring, and thus to increase its wear resistance.
[0033] In the present invention, oil is understood, on the one hand, to be aliphatic oils on a mineral oil basis, such as paraffin oil. In addition, the term oil also includes synthetic oils, such as silicone oil.
[0034] The residual porosity fraction can be determined, for example, by structural analysis and porosity measurement using image analysis methods.
[0035] The advantages achieved by the invention can be seen in particular by the fact that the composition of the sintered alloy according to the invention increases the thermal conductivity of the material. The above advantages are thus further increased. Best results are achieved when the thermal conductivity of the sintered alloy is greater than 40 W / mK, in particular when the sintered alloy is used as a valve seat ring. The thermal conductivity is therefore measured by the laser flash method (LFA - laser flash instrument).
[0036] The production of the component according to the invention, for example the production of a valve seat ring, is carried out by the following production steps:
[0037] Production of a powder mixture of hard phase, solid lubricant, pressing additive and copper-based powder. The copper-based powder and the hard phase are therefore preferably composed of water-atomized powder. The bulk density of the copper-based powder is preferably 2.4 g / ccm to 3.8 g / ccm. The average particle size of the copper-based powder is 25 μm to 160 μm, which can be measured by sieve analysis or by laser diffraction.
[0038] Pressing / compacting the powder mixture or producing a green body, respectively: Pressing is preferably carried out uniaxially. Pressing is preferably carried out to a relative density of 85% to 95% of the theoretical density of the material. The density is determined here by the weight and volume of the component.
[0039] Sintering of the component: The sintering of the component can be carried out in a conveyor furnace, a chamber furnace or a vacuum furnace. The sintering is preferably carried out in a temperature range of 850° C. to 1050° C., in a sintering atmosphere of a hydrogen and nitrogen mixture or an endothermic gas. During sintering, the maximum temperature is preferably reached in a time period of 15 minutes to 45 minutes. Infiltration of other copper-based powders can be carried out during the sintering process.
[0040] Calibration / further pressing process: A further pressing process is preferably carried out if the component does not meet the geometrical requirements (ie the quality of the component is set within tolerance by a new pressing).
[0041] Heat treatment: If a precipitation hardening alloy is used as the copper-based powder, a heat treatment is then carried out. Precipitation is formed thereby, increasing the strength and hardness of the material. The heat treatment is preferably carried out at a temperature of 250°C to 700°C for 1 hour to 16 hours.
[0042] Oil immersion: The parts are preferably impregnated with oil after heat treatment. Oil impregnation is preferably performed by an immersion process with a residence time in the oil of 2 minutes to 20 minutes. Impregnation can also be performed by negative pressure difference to better control the process.
[0043] Component machining: machining of areas of a component that do not meet the component geometry requirements, typically by grinding or turning. Preferably, the component is deburred by a sliding grinding process. DETAILED DESCRIPTION
[0044] The production of sintered shaped parts, in particular bearings or valve seat rings, from the sintered material according to the invention is carried out, for example, as follows:
[0045] Example 1 Valve seat ring with high thermal conductivity:
[0046] Here it is based on pure copper powder (purity > 99%) with an average particle size of 70 μm to 160 μm, which is mixed with 0.5% pressing additives, 2% solid lubricant MoS2 and 35% Fe-based hard phase (T10), and is subsequently pressed to a relative density of 93%, sintered at 980°C in a nitrogen-hydrogen atmosphere, and the front surface and AD are ground to the final size.
[0047] Example 2 Axial bearing in a turbocharger:
[0048] Here, it is based on a bronze alloy with a tin content of 10% and an average grain size of 60 μm to 150 μm, which is mixed with 0.5% pressing additives, 2% solid lubricant MnS and 20% Fe-based hard phase (T10), and is subsequently pressed to a relative density of 93%, sintered at 900°C in a nitrogen-hydrogen atmosphere, oil-impregnated at atmospheric pressure, previously surface-ground to the final size, and surface-structured by a new pressing / embossing process.
Claims
1. A wear-resistant, highly thermally conductive copper-based sintered alloy produced by powder metallurgy, wherein the sintered alloy is a powder mixture of a copper-based powder, a hard phase with a total content of 8% to 40% by weight, a solid lubricant with a total content of 0.4% to 3.8% by weight, a pressing additive with a total content of 0.3% to 1.5% by weight, and production-related impurities, characterized in that The powder mixture comprises at least 70% by weight of a copper-based powder, and The powder mixture also contains the following elements: 0.5 wt. % to 15 wt. % Zn, 0.5 wt. % to 12 wt. % Sn, 0.5 wt. % to 5 wt. % P, 0 wt. % to 15 wt. % Mn, 0.2 wt. % to 5 wt. % Si, 0 wt. % to 14 wt. % Al, 0.1 wt. % to 15 wt. % Ni and 0.5 wt. % to 8 wt. % Fe, as well as production-related impurities.
2. The sintered alloy according to claim 1, characterized in that: The hard phase includes one or more alloys selected from Fe-Mo, Fe-Mo-Si-Cr and / or Fe-Mo-Si-Cr-Ni-Mn, and production-related impurities.
3. The sintered alloy according to claim 1 or 2, characterized in that: The solid lubricant includes one or more lubricants selected from sulfide solid lubricants, hexagonal boron nitride, graphite and / or calcium fluoride.
4. The sintered alloy according to claim 1, characterized in that: The powder mixture further comprises the following elements and / or alloys: 1 wt % to 8 wt % Co, and / or 1 wt % to 8 wt % Mo.
5. The sintered alloy according to claim 1, characterized in that: The powder mixture further comprises the following components: 0.2 wt % to 2 wt % of tungsten oxide, molybdenum oxide, copper oxide and bismuth oxide, respectively.
6. The sintered alloy according to claim 1 or 2, characterized in that: The sintered alloy has at least 5% residual porosity, and at least 30% by volume of the residual porosity is filled with oil.
7. The sintered alloy according to claim 1 or 2, characterized in that: The sintered alloy has a thermal conductivity of >40 W / mK.
8. A method for manufacturing a sintered alloy according to any one of claims 1 to 7, characterized in that: The powder mixture is uniaxially compacted to form a green body and subsequently sintered at a temperature of 850°C to 1050°C in a sintering atmosphere of an endothermic gas.
9. The method according to claim 8, characterized in that After sintering, the sintered alloy is compacted or compressed again by a further pressing process.
10. The method according to claim 8 or 9, characterized in that: The sintered alloy is further heat treated at a temperature of 250°C to 700°C after sintering.
11. The method according to claim 8 or 9, characterized in that: In the sintering process, the material is infiltrated with other copper-based powders during powder metallurgy production.
12. The method of claim 8 or 9, wherein the endothermic gas is a mixture of hydrogen and nitrogen.
13. Use of the sintered alloy according to any one of claims 1 to 7 as a bearing or a valve seat ring.
Citation Information
Patent Citations
Ventilation seat ring
DE102016109539A1
Copper base sintered slide member
EP1975260A1
Sintered alloy valve guide and its production method
US20160160700A1
Valve seat ring
US20190143415A1
Sintered friction material, composite copper alloy powder used therefor and manufacturing method thereof
US5824923A